Traditional and Postmodern Perspectives: Samiha Khrais’s The Tree Stump as a Historical Novel - Yousef, Nisreen T. (Dirasat: Human and Social Sciences, 2024)
Objectives: This article aims to analyze The Tree Stump (1998; trans. 2019), a modern realist novel by the award-winning Jordanian writer Samiha Khrais, from both a historical-novel and postmodern perspective. Methods: The analysis is conducted against the backdrop of the viewpoints of key theorists of the historical novel, utilizing critical analysis and comparative analysis methods. Results: The results show that Khrais’s novel deploys as its main strategy of representing its historical events the techniques of the traditional/classic historical novel often associated with Walter Scott and his Waverly novels. Although The Tree Stump draws on myth, legend, and local folklore and mixes historical realism and magical realism, its main concern is the historical authenticity and factual accuracy of the events it describes. Conclusions: The Tree Stump contains the main characteristic features of a typical traditional historical novel as defined by the major theorists of historical fiction. It also combines elements of historical realism and magical realism without being impacted by the experimental writings of postmodernism.